Schwann cells acquire a repair phenotype after assembling into spheroids and show enhanced in vivo therapeutic potential for promoting peripheral nerve repair - Shih‐Heng Chen; Hsin‐Wen Wang; Pei‐Ching Yang; Shih‐Shien Chen; Chia‐Hsin Ho; Pei‐Ching Yang; Ying‐Chi Kao; Shao‐Wen Liu; Han Chiu; Yu‐Jie Lin; Er‐Yuan Chuang; Jen‐Huang Huang; et al. (Wiley, 2024)
Abstract The prognosis for postinjury peripheral nerve regeneration remains suboptimal. Although transplantation of exogenous Schwann cells (SCs) has been considered a promising treatment to promote nerve repair, this strategy has been hampered in practice by the limited availability of SC sources and an insufficient postengraftment cell retention rate. In this study, to address these challenges, SCs were aggregated into spheroids before being delivered to an injured rat sciatic nerve. We found that the three‐dimensional aggregation of SCs induced their acquisition of a repair phenotype, as indicated by enhanced levels of c‐Jun expression/activation and decreased expression of myelin sheath protein. Furthermore, our in vitro results demonstrated the superior potential of the SC spheroid‐derived secretome in promoting neurite outgrowth of dorsal root ganglion neurons, enhancing the proliferation and migration of endogenous SCs, and recruiting macrophages. Moreover, transplantation of SC spheroids into rats after sciatic nerve transection effectively increased the postinjury nerve structure restoration and motor functional recovery rates, demonstrating the therapeutic potential of SC spheroids. In summary, transplantation of preassembled SC spheroids may hold great potential for enhancing the cell delivery efficiency and the resultant therapeutic outcome, thereby improving SC‐based transplantation approaches for promoting peripheral nerve regeneration.